Analysis of ‘Flat-Earther’ Posts on Social Media: Reflections for Science Education from the Discursive Perspective of Foucault (Brazilian Journal of Research in Science Education, 2020)
In this paper we present the results of a research that aimed to analyze posts on a Twitter page of an organization that openly defends that the Earth is flat and to highlight its formative characteristics, as well as to discuss about the possible implications of such defense for Science Education. Discourse analysis was carried out based on the guidelines presented by Foucault and a priori theories were taken from the contributions of Feyerabend, Latour and Stengers. These choices occurred due to the fact that these contributions present heterodox points of view on the production of scientific knowledge, open to implications that are not only epistemological, which makes it possible to discuss the cultural, social and discursive complexity of the ‘flat Earth belief’. It is hoped that the considerations presented here may promote discussions related to the theme on the part of those who work in Science Education and, also, promote reflections on the very ethics of the scientific process and its limits.